Patient Experience of Nursing Quality in a Teaching Hospital in Saudi Arabia - Al Momani, M (Tehran University of Medical Sciences, 2012)
BACKGROUND: Examining the quality of nursing care from the patient's perspective is an important element in quality evaluation. The extent to which patients’ expectations are met will influence their perceptions and their satisfaction with the quality of care received. METHODS: A cross-sectional survey was conducted among admitted patients at King Khalid Teaching Hospital, Riyadh, Saudi Arabia. Data were collected (from January 2011 to March 2011) from a convenience sample of 448 patients using a 42-items questionnaire assessing six dimensions of the nursing care provided to, during hospitalization. RESULTS: On a four–point scale (4-higly agree,3-agree, 2-disagree, and 1-higly disagree). The individual items of nursing care showing the lowest means were the information received from the nurses about self-help (2.81), the information about the laboratory results (2.76) and the way the nurse shared the patient's feeling (2.72). A strong correlation existed between the overall perception level and the variables of gender (P=0.01), and the types of department (0.004). CONCLUSION: The findings of this study demonstrate negative experiences of patients with nursing care in dimensions of information, caring behavior, and nurse competency and technical care. Awareness of the importance of these dimensions of nursing care and ongoing support to investigate patients’ perception periodically toward quality of nursing care are critical to success the philosophy of patient centered health care.